Detection of Porcine Contamination in Beef Meatballs from Gedangan District Using PCR–RFLP - Suryadi, Gian Firdaus Putra; Astuti, Rahma Windi; Fitriani, Lilis Nur; Lisdiana, Lisa (Jurnal Biodjati, 2025)
Meatball is one of the popular meat dishes in Indonesia, especially in Sidoarjo. The sale of meatballs in Sidoarjo is carried out by Micro, Small, and Medium Enterprises (MSMEs), with 330 of the total 11,114 micro-traders selling meatballs. However, there is a risk of pork being adulterated into meatballs. This is a serious problem because Indonesia, especially Sidoarjo, is a Muslim-majority city with 95.5% of the total population of 2 million. Therefore, the purpose of this article is to conduct field checks to determine whether or not pork contamination is present in meatballs in Sidoarjo. Sampling locations were determined using a stratified random sampling method, which found that eight of the 15 villages, including Karangbong, Tebel, Sruni, Keboananom, Keboansikep, Gedangan, Ketajen, and Sawotratap Villages, have a significance value greater than the alpha value (0.05). Therefore, eight of them were used as sampling locations. One sample was purchased from each of the eight chosen villages, named S1, S2, S3, S4, S5, S6, S7, and S8. Meanwhile, the possibility of porcine contamination in beef meatball samples was analyzed using the Polymerase Chain Reaction - Restriction Fragment Length Polymorphism (PCR-RFLP) method with the restriction enzyme BsaJI. This study found that all eight samples and the negative control DNA amplicons were not cleaved by the BsaJI enzyme. Meanwhile, the positive control DNA amplicon was cleaved into 3 fragments. It was indicated that all samples and the negative control DNA amplicons were free of pork DNA contamination. Despite the anomaly, it can be concluded that all meatball samples bought from Gedangan District are not contaminated with pork. By demonstrating that meatballs from Sidoarjo are free from pork DNA, this study serves as an additional halal food monitoring in Sidoarjo. It reinforces public trust in local MSME food products.